Maximizing oil palm yield: innovation replanting strategies for sustainable productivity - Abubakar, Ahmed; Kasim, Susilawati; Ishak, Mohd Yusoff; Uddin, Md Kamal (Bilingual Publishing Co, 2023)
This paper examines the significance of innovative replanting strategies in maximizing oil palm yield whileensuring sustainable productivity. Through a comprehensive review of literature and analysis of current practices, themajor findings of this research highlighted the importance of advanced breeding and clonal selection in developinghigh-yielding and disease-resistant oil palm varieties. Precision agriculture technologies, including IoT devices,drones, and sensors, were identified as critical tools for data-driven decision making, optimizing resource efficiency,and reducing environmental impact. Sustainable land use planning and agroforestry integration emerged as keystrategies to balance productivity with environmental conservation. The broader impacts of this work extend to otheragricultural sectors and land use planning, offering valuable insights for policymakers and stakeholders to promoteresponsible and resilient agricultural practices. By embracing innovative replanting strategies, the oil palm industry cancontribute to a more sustainable and prosperous future, balancing economic growth with environmental stewardship.Continued research and collaboration are essential to achieve these goals and foster a harmonious coexistence betweenproductivity and sustainability, integrating precision agriculture technologies for resource optimization and reducedenvironmental impact, promoting sustainable land use planning and agroforestry integration to enhance biodiversityand ecosystem services. Strengthening collaborations between governments, industry players, and research institutionsfor innovation and knowledge exchange is essential.